Phase Conjugation in InSb(Cu) - Linnik, L.F.; Linnik, L.G.; Staryi, S.V. (Ukrainian Journal of Physics, 2022)
It is shown that the doping of narrow-band semiconductor InSb by copper leads to an enhancement of the phase conjugation efficiency at low intensities of laser radiation.